2020
DOI: 10.1002/cphc.202000747
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Reactivity of Supported ZnO Clusters: Undercoordinated Zinc and Oxygen Atoms as Active Sites

Abstract: The growth of ZnO clusters supported by ZnO-bilayers on Ag(111) and the interaction of these oxide nanostructures with water have been studied by a multi-technique approach combining temperature-dependent infrared reflection absorption spectroscopy (IRRAS), grazing-emission X-ray photoelectron spectroscopy, and density functional theory calculations. Our results reveal that the ZnO bilayers exhibiting graphite-like structure are chemically inactive for water dissociation, whereas small ZnO clusters formed on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
(133 reference statements)
0
6
0
Order By: Relevance
“…There should be another diminished band at approximately 1643 cm –1 that is blurred by the dramatically increasing background absorbance (which was more prominent on CuO X @p-ZnO in Figures B-b and ). These depletion bands can be all assigned to the adsorbed water molecules on p-ZnO: the broad band centered at 3190 cm –1 for the O–H stretching vibration (ν OH ), the 1643 cm –1 band for the bending vibration of the molecular adsorbed water (δ H2O ), and the 1518 and 1416 cm –1 bands for the bending vibration of the dissociated adsorbed water (δ Zn–OH ). , Additionally, considering the relatively low CO 2 reduction rate on p-ZnO in the activity test, it is suggested that on p-ZnO, water oxidation was much faster than the CO 2 reduction half of the reaction; therefore, since the holes and electrons were generated stoichiometrically, the dramatic consumption of holes by water oxidation leaves the residual electrons accumulated in the conduction band, observed as the background shift in the infrared spectra.…”
Section: Resultsmentioning
confidence: 99%
“…There should be another diminished band at approximately 1643 cm –1 that is blurred by the dramatically increasing background absorbance (which was more prominent on CuO X @p-ZnO in Figures B-b and ). These depletion bands can be all assigned to the adsorbed water molecules on p-ZnO: the broad band centered at 3190 cm –1 for the O–H stretching vibration (ν OH ), the 1643 cm –1 band for the bending vibration of the molecular adsorbed water (δ H2O ), and the 1518 and 1416 cm –1 bands for the bending vibration of the dissociated adsorbed water (δ Zn–OH ). , Additionally, considering the relatively low CO 2 reduction rate on p-ZnO in the activity test, it is suggested that on p-ZnO, water oxidation was much faster than the CO 2 reduction half of the reaction; therefore, since the holes and electrons were generated stoichiometrically, the dramatic consumption of holes by water oxidation leaves the residual electrons accumulated in the conduction band, observed as the background shift in the infrared spectra.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning its interaction with water, we recall that the ultrathin film of ZnO supported by Ag(111) does not hydroxylate, not even upon adsorption of molecular hydrogen or water . Furthermore, water molecules deposited on such an ultrathin ZnO film do not dissociate at the deposition and scanning temperatures between 130 and 160 K used here …”
Section: Resultsmentioning
confidence: 84%
“…3 Furthermore, water molecules deposited on such an ultrathin ZnO film do not dissociate at the deposition and scanning temperatures between 130 and 160 K used here. 31 D 2 O at a local coverage between 7% ML to 14% ML forms clusters on the ZnO islands of the partially covered ZnO/ Ag(111) surface (Figure 1a−c). Two different cluster densities exist in Figure 1a.…”
Section: Resultsmentioning
confidence: 99%
“…36) and Pt(111), 37 while ZnO lms on other metals, such as Ag(111), are less susceptible to hydroxylation, and no structural transformation has been observed under similar conditions. 38,39 Motivated by the above considerations, we analyze ZnO, ZnOOH, Zn(OH) 5/6 , Zn(OH), and Zn(OH) 3/2 lms on Ag, Au, Cu, Ir, Pd, Pt and Rh(111) substrates. The specic stoichiometries are selected based on the experimental literature and our previous experimental/theoretical study of the ZnO/Pd(111) system.…”
Section: Introductionmentioning
confidence: 99%
“…36) and Pt(111), 37 while ZnO films on other metals, such as Ag(111), are less susceptible to hydroxylation, and no structural transformation has been observed under similar conditions. 38,39…”
Section: Introductionmentioning
confidence: 99%